Curriculum Change and Self-Governing Agreements: A Yukon First Nation Case Study - Lewthwaite, Brian Ellis; Owen, Thomas; Doiron, Ashley (International Journal of Multicultural Education, 2015)
Recent developments in Canada’s Yukon Territory draw attention to how political changes have potential for accelerating practices in education that are responsive to Indigenous Peoples’ cultural knowledge systems and practices. In this study, through the use of case study methodology, an account of the changes that have occurred in one First Nation are presented. Further, the study seeks to identify the processes influencing the development. Finally, tensions at the classroom, school, and community levels arising from these changes and anticipated changes are described.